2020
DOI: 10.3390/jmse8110900
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Cold Front-Generated Waves in the Coastal Louisiana

Abstract: Atmospheric cold front-generated waves play an important role in the air–sea interaction and coastal water and sediment transports. In-situ observations from two offshore stations are used to investigate variations of directional waves in the coastal Louisiana. Hourly time series of significant wave height and peak wave period are examined for data from 2004, except for the summer time between May and August, when cold fronts are infrequent and weak. The intra-seasonal scale variations in the wavefield are sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The arrival of anticyclonic cold fronts typically occurs between September and April and can extend as far south as 10°N latitude (DiMego et al, 1976). These cold fronts are associated with a significant increase in wind intensity, cloud cover, atmospheric pressure, wave height, and a decrease in temperature (Appendini et al, 2014(Appendini et al, , 2018Cao et al, 2020;Ortiz-Royero et al, 2013). Considering the strong northerly wind component during cold fronts, they could influence the particle transport by displacing them toward the south, impending them to reach areas such as the Yucatan Peninsula.…”
Section: Table 1 Lagrangian Experiments Results For Each Zone Within ...mentioning
confidence: 99%
“…The arrival of anticyclonic cold fronts typically occurs between September and April and can extend as far south as 10°N latitude (DiMego et al, 1976). These cold fronts are associated with a significant increase in wind intensity, cloud cover, atmospheric pressure, wave height, and a decrease in temperature (Appendini et al, 2014(Appendini et al, , 2018Cao et al, 2020;Ortiz-Royero et al, 2013). Considering the strong northerly wind component during cold fronts, they could influence the particle transport by displacing them toward the south, impending them to reach areas such as the Yucatan Peninsula.…”
Section: Table 1 Lagrangian Experiments Results For Each Zone Within ...mentioning
confidence: 99%
“…The pre‐frontal phase characterized by southerly winds (Figure S6c in Supporting Information S1) anticipates the frontal passage where the wind direction quickly shifts to northerly winds in the post‐frontal phase (Figure S6c in Supporting Information S1) (Moeller et al., 1993). Previous research has shown that winter storms in coastal Louisiana and in particular cold fronts control the wave fields (Cao et al., 2020; Guo et al., 2020), water fluxes (Feng & Li, 2010), and sediment exchange (Dingler & Reiss, 1990; Perez et al., 2000; Roberts et al., 1989). Reed (1989), using sediment deposition measurements in Terrebonne Bay, suggested that cold fronts represent an ideal setting for sediment deposition.…”
Section: Discussionmentioning
confidence: 99%
“…The daily tidal amplitude average is 0.32 m at the coast and 0.03 m at the upper basin; this tidal range is significantly influenced by wind during the winter season when cold fronts occur at 3-7 days duration while tidal oscillation is the main driver during the summer season [49,54,55]. Cold fronts in coastal Louisiana are characterized by a strong wind shear, an abrupt drop in atmospheric pressure, and a fast reduction in air temperature [56]. Although cold fronts are not as severe as tropical cyclones, wind direction/velocity control water levels and circulation, sediment transport (e.g., fluxes, wetland accretion/erosion, sediment resuspension), and the exchange of organic matter and nutrients between the BB complex and the GOM [38,56].…”
Section: Area Descriptionmentioning
confidence: 99%
“…Cold fronts in coastal Louisiana are characterized by a strong wind shear, an abrupt drop in atmospheric pressure, and a fast reduction in air temperature [56]. Although cold fronts are not as severe as tropical cyclones, wind direction/velocity control water levels and circulation, sediment transport (e.g., fluxes, wetland accretion/erosion, sediment resuspension), and the exchange of organic matter and nutrients between the BB complex and the GOM [38,56]. Because of the BB complex location in sub- The main freshwater inputs into the basin are rainwater, surface runoff from surrounding areas, the Gulf Intracoastal Waterway, and the Davis Pond Freshwater Diversion (DPFD) located in the upper basin with a maximum operational discharge of 250 m 3 s −1 [53,54].…”
Section: Area Descriptionmentioning
confidence: 99%